2016
DOI: 10.1016/j.neurobiolaging.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide assessment of Parkinson's disease in a Southern Spanish population

Abstract: Here, we set out to study the genetic architecture of Parkinson’s disease (PD) through a Genome-Wide Association Study (GWAS) in a Southern Spanish population. 240 PD cases and 192 controls were genotyped on the NeuroX array. We estimated genetic variation associated with PD risk and age at onset (AAO). Risk profile analyses for PD and AAO were performed using a weighted genetic risk score (GRS). Total heritability was estimated by genome-wide complex trait analysis. Rare variants were screened with single-var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 46 publications
4
31
2
Order By: Relevance
“…The SNP with the strongest association in Stage 1 (rs17763050, p = 2.74 x10 -9 ) is in high LD with the known H1/H2 haplotype tag SNP rs8070723 (SI Fig 7E). Both SNPs are associated with ORs ~0.75 (95% CI ± 0.1) for the H2 haplotype, and OR 1.22 (95% CI ± 0.1) for the H1 haplotype (SI Table 6), consistent with previously reported effect sizes 3,5 . Due to a smaller cohort size and consequent lack of power, the association with 17q21.31 is less prominent in Stage 2 data.…”
Section: Pd Does Not Share the Same Risk-associated H1 Variants As Pspsupporting
confidence: 89%
“…The SNP with the strongest association in Stage 1 (rs17763050, p = 2.74 x10 -9 ) is in high LD with the known H1/H2 haplotype tag SNP rs8070723 (SI Fig 7E). Both SNPs are associated with ORs ~0.75 (95% CI ± 0.1) for the H2 haplotype, and OR 1.22 (95% CI ± 0.1) for the H1 haplotype (SI Table 6), consistent with previously reported effect sizes 3,5 . Due to a smaller cohort size and consequent lack of power, the association with 17q21.31 is less prominent in Stage 2 data.…”
Section: Pd Does Not Share the Same Risk-associated H1 Variants As Pspsupporting
confidence: 89%
“…In brief, PRS profiling is calculated traditionally based on weighted allele dose manner as per previous work. [25][26][27][28][29][30][31][32] We used the R package PRSice2. 33 Permutation testing and P-value aware LD pruning was used to identify best P thresholds in external GWAS data to construct the PRS, allowing us to utilize variants below the common GWAS significance threshold of 5E-08.…”
Section: Polygenic Risk Profiles Versus Disease Status and Age At Onsetmentioning
confidence: 99%
“…Although common genetic polymorphisms in the vicinity of the ACMSD gene were previously shown to be associated with increased risk for PD by several GWAS studies [1][2][3][4], we know of no reports on specific mutation in this gene in patients with sporadic PD. Recently, a stop codon ACMSD mutation (p.Trp26Stop) has been reported in a family with cortical myoclonus, epilepsy, and parkinsonism [5].…”
Section: Discussionmentioning
confidence: 99%
“…The first large-scale meta-analysis of GWAS in PD nominated single nucleotide polymorphisms (SNP) in five new susceptibility loci including ACMSD, STK39, MCCC1/LAMP3, SYT11, and CCDC62/HIP1R [1]. The association of ACMSD, aminocarboxymuconate semialdehyde decarboxylase, variants and PD has been later replicated by different groups [2][3][4]. A recent study has reported a rare ACMSD stop codon mutation (p.Trp26Stop) in a family with autosomal-dominant cortical myoclonus, epilepsy, and parkinsonism [5].…”
Section: Introductionmentioning
confidence: 99%